Soil Characterization of Kanker District: A Transect Study along a Toposequence - N. Kumar (Journal of the Indian Society of Soil Science, 2023)
Pedological investigation carried out on a soil toposequence of Bastar Plateau in Kanker district of Chhattisgarh state and landform-soil relationships were established. Five soil profiles, representative of the summit, shoulder slope, pediments and upper and lower pediplains in a toposequence were studied. The study indicated that the soil development and its properties were following the toposequence. The profile development was least at the summit and best in the pediplains of the toposequence. The horizon sequences observed were Ap-Cr, Ap-Bw-BC, Ap-Bw-Cr and Ap-Bw-Bss from summit through the pediplains. The soil colour varied from reddish to dark gray down the toposequence. The solum depth varied from extremely shallow to very deep. An increasing trend was observed in clay content, cation exchange capacity, soil reaction, electrical conductivity, base saturation, and exchangeable cations from summit through the pediplains. The soils of summit, pediments and pediplains were classified as Entisols, Inceptisols and Vertisols, respectively.